2018
DOI: 10.1039/c8ce00655e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonded organic frameworks: design, structures and potential applications

Abstract: This paper highlights the current key progress on HOF-based materials, including their design, structural characteristics, and applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(161 citation statements)
references
References 86 publications
2
157
0
2
Order By: Relevance
“…Following the idea that COFs lie in a continuous spectrum between amorphous networks made from irreversible covalent bonds and organic single crystals composed of van der Waals interactions, it is not surprising that similar crystalline networks can be synthesized from hydrogen bonding interactions. Such materials, referred to as hydrogen‐bonded organic frameworks (HOFs), were pioneered by Wuest in the 1990s and have been popularized recently due to their potential applications in gas separation and storage . One of the earliest HOF examples was an organic diamondoid network formed from a tetraphenylmethane derivative through the N−H⋅⋅⋅O hydrogen bonds between terminal 2‐pyridone groups .…”
Section: Additional Examples Of Polymer Network With Unique Chemistrmentioning
confidence: 99%
“…Following the idea that COFs lie in a continuous spectrum between amorphous networks made from irreversible covalent bonds and organic single crystals composed of van der Waals interactions, it is not surprising that similar crystalline networks can be synthesized from hydrogen bonding interactions. Such materials, referred to as hydrogen‐bonded organic frameworks (HOFs), were pioneered by Wuest in the 1990s and have been popularized recently due to their potential applications in gas separation and storage . One of the earliest HOF examples was an organic diamondoid network formed from a tetraphenylmethane derivative through the N−H⋅⋅⋅O hydrogen bonds between terminal 2‐pyridone groups .…”
Section: Additional Examples Of Polymer Network With Unique Chemistrmentioning
confidence: 99%
“…Apart from POPs, another family of porous organic materials being applied for hydrocarbon separations are hydrogen‐bonded organic frameworks (HOFs). Instead of being connected by covalent bonds like POPs, the 3D porous networks of HOFs are the supramolecular assembly of organic building blocks (tectons) bridged together via the cooperative strong interactions of hydrogen bonds . A classic example of HOFs for olefin/paraffin separations is HOF‐4 reported by Li et al The sixfold framework interpenetration completely blocks the channels in the directions, leaving 1D channels with openings of 3.8 × 8.1 Å 2 along the crystallographic b ‐axis.…”
Section: Other Porous Materials For Adsorptive Light Olefin/paraffin mentioning
confidence: 99%
“…Instead of being connected by covalent bonds like POPs, the 3D porous networks of HOFs are the supramolecular assembly of organic building blocks (tectons) bridged together via the cooperative strong interactions of hydrogen bonds. [166] A classic example of HOFs for olefin/paraffin separations is HOF-4 reported by Li et al [167] The sixfold framework interpenetration completely blocks the channels in the [101] directions, leaving 1D channels with openings of 3.8 × 8.1 Å 2 along the crystallographic b-axis. Singlecomponent gas sorption measurement showed that the activated HOF-4a preferentially adsorbs ethylene over ethane up to ambient pressure at 296 K. IAST calculations further predicted that HOF-4a has a C 2 H 4 /C 2 H 6 adsorption selectivity of 14 for an equimolar gas mixture at room temperature and 1 atm, which is comparable to that of Na-ETS-10.…”
Section: Porous Organic Materialsmentioning
confidence: 99%
“…Der Idee folgend, dass COFs in einem kontinuierlichen Spektrum zwischen amorphen Netzwerken auf der Basis von irreversiblen kovalenten Bindungen und organischen Einkristallen auf der Basis von Van‐der‐Waals‐Wechselwirkungen liegen, ist es nicht überraschend, dass ähnliche kristalline Netzwerke über Wasserstoffbrücken synthetisiert werden können. In den 1990er Jahren bereitete Wuest den Weg für derartige Materialien, die als organische Gerüste mit Wasserstoffbrücken (HOFs, hydrogen‐bonded organic frameworks) bezeichnet werden, und in letzter Zeit wurden sie aufgrund ihrer potenziellen Anwendungen bei der Gastrennung und ‐speicherung populär . Eines der ersten Beispiele von HOFs war ein organisches diamantoides Netzwerk, das aus einem Tetraphenylmethan‐Derivat über N‐H⋅⋅⋅O‐Wasserstoffbrücken zwischen endständigen 2‐Pyridon‐Gruppen gebildet wurde .…”
Section: Beispiele Von Polymernetzwerken Mit Speziellen Chemisch/struunclassified
“…In den 1990er Jahren bereitete Wuest den Wegf ür derartige Materialien, die als organische Gerüste mit Wasserstoffbrücken (HOFs,h ydrogen-bonded organic frameworks) bezeichnet werden, und in letzter Zeit wurden sie aufgrund ihrer potenziellen Anwendungen bei der Gastrennung und -speicherung populär. [256] Eines der ersten Beispiele von HOFs war ein organisches diamantoides Netzwerk, das aus einem Te traphenylmethan-Derivat über N-H···O-Wasserstoffbrücken zwischen endständigen 2-Pyridon-Gruppen gebildet wurde. [257] Die schwachen Wasserstoffbrücken in HOFs ermçglichen die Bildung großer Einkristalle,b egrenzen jedoch stark ihre Stabilität.…”
Section: Angewandte Chemieunclassified